Kekuatan Pembuktian Akta Dibawah Tangan yang Telah Diregistrasi oleh Notaris (Waarmerking) di Kabupaten Maros - Ibnu Izzah (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
waarmarked in less than 5 years by 9 Notaries. This indicates that people in Maros Regency have a high interest in registering deeds under their hands at a Notary. Then what if the underhanded deed has been registered or recorded by a notary (waarmerking) who incidentally is an authorized public official, will it add to the strength of proof of the underhanded deed. This study aims to: (1) find out the practice and responsibilities of a notary in registering deed under the hands of a waarmerking (2) understand the strength of proof of an underhanded deed that has been registered by a notary in civil court proceedings. The research method used in this research is empirical legal research, namely research that prioritizes field research which aims to obtain primary data through interviews with several Notaries and Judges in Maros Regency. The data were then analyzed qualitatively. The results of this study indicate that: (1) Notaries are not legally responsible for the correctness of privately registered deeds (waarmerking) both from the truth of their identity, the contents of the deed, the date of manufacture and the signatures of the parties. So that the Notary cannot be prosecuted both civilly and criminally for untruths in the underhanded deed that has been waarmarked (2) The strength of proof of underhanded deed that has been waarmarked cannot be equated with an authentic deed. Instead, it remains a private deed, the perfection of which lies in the acknowledgment of the signature by the parties who sign the private deed.